MECHATRONIC-MODULAR ROBOT MOVEMENT VISUALIZATION - Pavel V. Gerasin; Yulia S. Redko; Vladimir V. Martynov (Advanced Engineering Research, 2011)
The urgency and application of the single-type modular robots is considered. The kinematical model-based program of such robot movement visualization is worked out. The obtained results can be used for the development of the intelligent manipulation of the robot movement.